Beyond the Commons: Investigating the Value of Personalizing Web Search - Teevan, Jaime; Dumais, Susan; Horvitz, Eric (Proceedings PIA 2005: Workshop on New Technologies for Personalized Information Access, 2005)
We investigate the diverse goals people have when they issue the same query to a Web search engine, and the ability of current search tools to address such diversity, in order to understand the potential value of personalizing search results. Great variance was found in the results different individuals rated as relevant for the same query—even when those users expressed their underlying informational goal in the same way. The analysis suggests that, while current Web search tools do a good job of retrieving results to satisfy the range of intentions people may associate with a query, they do not do a very good job of discerning an individual’s unique search goal. We discuss the implications of this study on the design of search systems and suggest areas for additional research.